Securing Home Base: Separation-Individuation, Attachment Theory, and the "Virtual Worlds" Paradigm in Video Games. Issue 1 (31st March 2017) - Goetz, Christopher
ABSTRACT: This paper identifies the "virtual worlds" paradigm in psychoanalytic approaches to video games. Sometimes counterproductive to game interpretation, this paradigm views all games as an escape into separate and substitutive virtual reality. I argue that the virtual worlds framework only applies to some video games, and rarely encapsulates most games' address to the player. I propose an alternative approach based in separation-individuation and attachment theory, pointing to how a wide variety of games provide players with "secure base" experiences as a form of affect regulation and metacognition. Introducing three broad categories of tether fantasies in video games—lifeline, home base, and perpetuum mobile—, I map out some of the generic terrain of commercial games from a secure base perspective, emphasizing the value of going and coming in the process of developing autonomy. I argue that the tether fantasy in video games not only illustrates the integration of attachment and separation-individuation schools of thought, but also offers a compelling reason to reconsider the analytical meaning of video game play. The paper's analysis of Minecraft as a home base tether game also explores the question of how games can themselves serve as an anchor for ventures into more complicated social worlds at times of transition like nest-leaving, or for times of stress in adult life.